TOURISM AS A FACTOR OF SUSTAINABLE DEVELOPMENT OF RURAL AREAS BELONGING TO RUDNIČKA MORAVA - Ristić, Lela; Vujičić, Milan; Leković, Miljan (Economics of Agriculture, 2016)
The paper looks at tourism as an essential component of sustainable development of rural areas belonging to Rudnička Morava territory. The aim of the paper is to point to the role of tourism in the integration of rural areas into the national and international economy based on the analysis of the relevant rural development model and in terms of more effcient endogenous development. The main hypothesis is that rural areas belonging to Rudnička Morava territory have signifcant natural and anthropogenic resources for tourism development. However, what lacks is an integrated strategy that would contribute to sustainability and strengthening of the competitiveness of the rural economy. In accordance with the subject of the paper, its aim and the set hypotheses, qualitative, quantitative and SWOT analysis were applied during the research. A survey was conducted in order to obtain positions and feedback from the key actors involved in tourism development. The paper is organized in eight sections. The main result of the research points to the necessity of giving priority to rural tourism development as an essential component of the revitalization of villages and local communities.